Relationship between knowledge and practice on hydration among Perak shooters - Hazni, Muhammad Al-Nazirul Hanis; Razali, Muhammad Akmal Hazim; Ahmad Anajmi, Emma; Ismail, Ahmad Dzulkarnain; Kamaruddin, Harris Kamal; Abu Bakar, Al Hafiz (Universiti Teknologi MARA, Perlis, 2025)
Hydration plays an important role in maintaining the performance and cognitive function of athletes. However, there is limited research on the relationship between hydration knowledge and practice among shooters, particularly in the state of Perak. Hence, this study aims to investigate the correlation between hydration knowledge and hydration practices among Perak shooters. Thirty-two shooters (age: 16 ± 2 years) were assessed for hydration levels using Urine Specific Gravity (USG) measurements and were surveyed using the Hydration Knowledge Scale (HyKS) to evaluate their understanding of hydration principles. The selection criteria included active shooters who participated in state-level competitions. The study found a significant moderate negative correlation between total hydration knowledge scores and USG levels (p < 0.01). This suggests that individuals with moderate hydration knowledge tend to exhibit better hydration practices. Furthermore, increased knowledge about hydration appears to contribute to improved hydration habits, which may enhance shooting accuracy and overall performance. Future research should use accurate methods to check hydration for small populations such as blood osmolality or wearable devices.